2020
DOI: 10.1186/s12871-020-01022-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of intraoperative hyperglycemia and postoperative outcomes in patients undergoing non-cardiac surgery: a multicenter retrospective study

Abstract: Background: While pre and postoperative hyperglycemia is associated with increased risk of surgical site infection, myocardial infarction, stroke and risk of death, there are no multicenter data regarding the association of intraoperative blood glucose levels and outcomes for the non-cardiac surgical population. Methods: We conducted a retrospective cohort study from the Michigan Surgical Quality Collaborative, a network of 64 hospitals that prospectively collects validated data on surgical patients for the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Perioperative hyperglycemia is associated with increased morbidity and mortality [5] . Regarding the intraoperative hyperglycemia, no difference in postoperative outcomes was detected between intraoperative blood glucose levels of more or less than 180mg/dl but intraoperative blood glucose of 250mg/dL was a predictor of 30-day mortality/ morbidity [6] .…”
Section: Introductionmentioning
confidence: 80%
“…Perioperative hyperglycemia is associated with increased morbidity and mortality [5] . Regarding the intraoperative hyperglycemia, no difference in postoperative outcomes was detected between intraoperative blood glucose levels of more or less than 180mg/dl but intraoperative blood glucose of 250mg/dL was a predictor of 30-day mortality/ morbidity [6] .…”
Section: Introductionmentioning
confidence: 80%
“…It has been estimated that between 15 and 20% of surgical patients have undiagnosed diabetes or impaired fasting glucose which does not necessarily affect postoperative outcomes [ 92 , 93 ] unless the plasma glucose level was ≥250 mg/dL, which was associated with higher 30-day morbidity/mortality [ 94 ]. Glucose management in patients with and without diabetes could be impacted by oral carbohydrate and dexamethasone administration.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Silinskie et al, although hypoglycemia occurred in patients receiving regular and glargine insulin, it was similar in both groups ( 4 ). Nevertheless, hypoglycemia was reported in the study by Hagelberg et al in patients receiving regular insulin ( 9 ), and in the study by Guillermo et al, hypoglycemia was more common in patients receiving glargine ( 7 ). Despite these studies, based on the results of the current study, hypoglycemia was not observed in any of the patients in the two groups.…”
Section: Discussionmentioning
confidence: 96%